Unveiling the Derivative of cot(x) using the Quotient Rule and Trigonometric Identities

d/dx cotx

To find the derivative of cot(x), we can use the quotient rule

To find the derivative of cot(x), we can use the quotient rule. The quotient rule states that for two functions u(x) and v(x),

(d/dx) [u(x) / v(x)] = [v(x) * u'(x) – u(x) * v'(x)] / [v(x)]^2.

In this case, let u(x) = 1 and v(x) = tan(x).

Therefore, u'(x) = 0 (since the derivative of a constant is zero),
and v'(x) = sec^2(x) (since the derivative of tan(x) is sec^2(x)).

Applying the quotient rule, we have:

(d/dx) [cot(x)] = [(tan(x) * 0) – (1 * sec^2(x))] / [tan(x)]^2.

Simplifying this expression, we get:

(d/dx) [cot(x)] = -sec^2(x) / tan^2(x).

Now, we can use the trigonometric identity tan^2(x) + 1 = sec^2(x) to simplify the result:

(d/dx) [cot(x)] = -sec^2(x) / [tan^2(x)] * (tan^2(x) + 1) / (tan^2(x) + 1).

Simplifying further, we get:

(d/dx) [cot(x)] = -1 / (sin^2(x) / cos^2(x) + 1).

Next, we can simplify the denominator:

(d/dx) [cot(x)] = -1 / [(sin^2(x) + cos^2(x)) / cos^2(x)].

Using the trigonometric identity sin^2(x) + cos^2(x) = 1, we have:

(d/dx) [cot(x)] = -1 / (1 / cos^2(x)).

Finally, simplifying the expression, we get:

(d/dx) [cot(x)] = -cos^2(x).

Therefore, the derivative of cot(x) is -cos^2(x).

More Answers:

Understanding the Square Root Parent Function and Its Graph: A Fundamental Guide for Mathematical Applications
The Chain Rule: How to Differentiate the Cosine Function (cos(x)) with respect to x
Unlocking the Power of Calculus: How to Find the Derivative of sin(x)

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded


Recent Posts

Don't Miss Out! Sign Up Now!

Sign up now to get started for free!